What a good boy! Deciphering the efficiency of detection dogs - Martin, Clément; Willem, Noémie; Desablens, Sorenza; Menard, Vincent; Tajri, Sophia; Blanchard, Solène; Brostaux, Yves; Verheggen, François; Diederich, Claire (Frontiers in Analytical Science, 2022)
Dogs have a powerful olfactory system, which is used in many areas of the police and military to detect drugs, human remains, and explosives, among other items. Despite these powerful detection abilities, methods assessing the performance (MAP) of dogs remain scarce, and have never been validated. In particular, scientific knowledge on post-training performance assessments is scarce. To validate a quantitative MAP, an efficient detection dog (DD) must first be defined. Here, we aimed to define what an efficient DD is, and to develop a quantitative MAP. Specifically, we conducted 1) an international survey sent to professional DD practitioners (n = 50), and 2) an experimental assay on cadaver and drug DDs (n = 20). Based on the survey, efficient DDs were defined as confident animals, making few mistakes, alerting to the presence of target odors as close as possible, able to strategically screen the search area effectively, independent and not easily distracted. The developed quantitative MAP was based on video tracking DDs in a circular behavioral arena, in which the error rate of DD was recorded, including accuracy and the strategy level. Previous studies have already demonstrated that DDs are usually confidant. Guidance was not assessed during MAP development; however, handlers could not guide DDs during the search session. Based on this method, future studies should evaluate DD performance throughout the entire training process. Such monitoring would allow thresholds to be determined, allowing efficient DDs to be identified, along with the effect of certain factors on performance (e.g., dogs breed, gender, and training aids used during DD conditioning).